(3GdNdGUI aj Yde GdcdGes ((3GdfLa s)
(3ChdgG (B:s
(3GYde Gf gPG GdcJGH jTJed Ydi eSGFd JYdb HYde GdCUhd ef GdJhMjO hGdYOd hGdfHhI s
(3BNQgG (B:s
(3hPdc eMGd aKHJ Cfge ZjQ ecdajf Hd efYejf ecQejf Je cJGH GdNdGUI HMeO Gddg hefg s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B- (3GdfLa (B(12/298) s
Keywords: (3GdJhMjO hGdedd hGdfMds